The joy of the Gospel : Evangelii gaudium - apostolic exhortation - Francis, Pope, 1936-2025; Catholic Church. Pope (2013-2025 : Francis) (Washington, D.C.: United States Conference of Catholic Bishops, 2013)
"From a discussion of economic justice to a call for new decision-making roles for women in the Church, The Joy of the Gospel is thought provoking, wide-ranging, and challenging to every Catholic. Those who carefully read it, study it, and pray with it will be ready to take up, with the whole Church, this "new phase of evangelization, one marked by enthusiasm and vitalilty"--and, most especially, joy"--Publisher.
Introduction. A joy ever new, a joy which is shared -- The delightful and comforting joy of evangelizing -- The new evangelization for the transmission of the faith -- The church's missionary transformation. A church which goes forth -- Pastoral activity and conversion -- From the heart of the Gospel -- A mission embodied within human limits -- A mother with an open heart -- Amid the crisis of communal commitment. Some challenges of today's world -- Temptations faced by pastoral workers -- The proclamation of the Gospel. The entire people of God proclaims the Gospel -- The homily -- Preparing to preach -- Evangelization and the deeper understanding of the kerygma -- The social dimension of evangelization. Communal and societal repercussions of the kerygma -- The inclusion of the poor in society -- The common good and peace in society -- Social dialogue as a contribution to peace -- Spirit-filled evangelizers. Reasons for a renewed missionary impulse -- Mary, mother of evangelization.
Keywords: Catholic Church -- Doctrines; Evangelistic work -- Catholic Church; Joy -- Religious aspects -- Catholic Church; Economics -- Religious aspects -- Catholic Church; Church and social problems -- Catholic Church; Income distribution -- Religious aspects -- Catholic Church; Poverty -- Religious aspects -- Catholic Church